Synthesis, characterization and catalytic activity of Cu(II), Co(II), Ni(II), Mn(II) and Fe(III) complexes of 4-((3-formyl-4-hydroxyphenyl)diazenyl)-N-(4-methyloxazol-2-yl) benzenesulfonamide - Hanafy, Ahmed Imam; Hassan, Ali Mostafa Ali; Shama, Sayed Ahmed; Thabet, Hamdy Khamees; El-alfy, Hany Mohammad Zaky (European Journal of Chemistry, 2013)
The sulfonamide derivative, 4-((3-formyl-4-hydroxyphenyl)diazenyl)-N-(4-methyloxazol-2-yl) benzenesulfonamide (FDMB), was synthesized and characterized. Additionally, its Cu(II), Co(II), Ni(II), Mn(II) and Fe(III) complexes were prepared and their structures were investigated by elemental analysis, thermal analysis and (IR, electronic and EPR) spectroscopy. The mode of binding indicates that the ligand binds to the metal ion through carbonyl oxygen and OH phenolic with displacement of its proton. The Co(II) complex was applied for the hydrolysis of nerve agent-like compound, bis-(p-nitrophenyl) phosphate (BNPP). The results showed a significant rate enhancement of 2.5 million fold with respect to the auto-hydrolysis of BNPP under the same conditions.